Improvement of stability of Nb3Sn superconductors by introducing high specific heat substances. (24th January 2018) - Xu, X; Li, P; Zlobin, A V; Peng, X
Abstract: High- J c Nb3 Sn conductors have low stability against perturbations, which accounts for the slow training rates of high-field Nb3 Sn magnets. While it is known that adding substances with high specific heat ( C ) into Nb3 Sn wires can increase their overall specific heat and thus improve their stability, there has not been a practical method that is compatible with the fabrication of long-length conductors. In this work, we put forward a scheme to introduce such substances to distributed-barrier Nb3 Sn wires, which adds minimum difficulty to the wire manufacturing process. Multifilamentary wires using a mixture of Cu and high- C Gd2 O3 powders have been successfully fabricated along this line. Measurements showed that addition of Gd2 O3 had no negative effects on residual resitivity ratio or non-Cu J c, and that flux jumps were remarkably reduced, and minimum quench energy values at 4.2 K, 14 T were increased by a factor of three, indicating that stability was significantly improved. We also discussed the influences of the positioning of high- C substances and their thermal diffusivity on their effectiveness in reducing the superconductor temperature rise against perturbations. Based on these results, we proposed an optimized conductor architecture to maximize the effectiveness of this approach.